ANALISIS MATERI PENDIDIKAN BERKARAKTER DALAM PEMBELAJARAN SOSIOLOGI PADA SMA KOTA BANDA ACEH - Abubakar, Abubakar; Anwar, Anwar (UNIVERSITAS SERAMBI MEKKAH, 2015)
Abstract Begin 1976 the sociology officially became the subjects in senior high school, the main problem is not the availability of learning that teachers have a background of sociology, this led to a lack of ability of teachers in preparing and teaching material models based on local wisdom, learning is often focused on textbooks alone, so that the development paradigm character education can not be realized, unattractive and boring lessons, students learned much from the local values and life experiences, this study is one of the important effort to find the exact model of learning with the learning principles of sociology and the availability of teaching materials which corresponds the paradigm of character education and be able to identify various barriers and were able to find a way out. This research method is descriptive qualitative triangulation approach, results show, shows, Implementation character values based on local wisdom in teaching sociology in Banda Aceh has some problems and become obstacles are: The existence of a standard regulatory measurement of national education through the national final examination (standardized testing) which emphasizes the realm koqnitif course, this raises the contradictory because it is centralized, making it hard Implementation indigenous values that are decentralized. Teachers do not have the experience of teaching sociology, they are not in field of sociology, teaching sociology is additional subjects other than teaching main task in mayority, with such conditions are often the task of teaching sociology courses in Banda Aceh is a double play (multiple roles). The material used is a national and centralized textbooks, teachers have not been able to develop special materials in the classroom-based learning in the region. Many parents no longer pay attention to their children's education in every school, they assume teenager education is the responsibility of school, the task of parents is to deliver and finance only. Key Words : Teaching Caracter Value and Local Wisdom